2023
DOI: 10.1097/eja.0000000000001902
|View full text |Cite
|
Sign up to set email alerts
|

Remimazolam and serious adverse events

Sander Kempenaers,
Tom G. Hansen,
Marc Van de Velde

Abstract: Remimazolam is anticipated to be an interesting anaesthetic and sedative. It combines the pharmacodynamic properties of midazolam with pharmacokinetic properties similar to remifentanil. However, worrisome case reports of anaphylaxis, delayed emergence and re-sedation have emerged recently and necessitate further investigation. PubMed (including MEDLINE) and EMBASE were searched for all studies reporting serious adverse events where remimazolam was administered for sedation or anaesthesia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 138 publications
0
3
0
Order By: Relevance
“…First, the majority of existing studies are small-scale and heterogeneous, limiting the generalizability of their findings. Thus, for obvious reasons and due to some unusual pharmacological effects observed in certain adults (e.g., delayed recovery and anaphylaxis), [28][29][30][31] In conclusion, this scoping review demonstrated that the current evidence is insufficient to either endorse or refute the clinical use of remimazolam in children, despite preliminary evidence suggesting its efficacy and safety. Further research is needed to address knowledge gaps, establish standardized protocols, and ensure the optimal utilization of remimazolam in pediatric sedation and anesthesia.…”
Section: Discussionmentioning
confidence: 85%
“…First, the majority of existing studies are small-scale and heterogeneous, limiting the generalizability of their findings. Thus, for obvious reasons and due to some unusual pharmacological effects observed in certain adults (e.g., delayed recovery and anaphylaxis), [28][29][30][31] In conclusion, this scoping review demonstrated that the current evidence is insufficient to either endorse or refute the clinical use of remimazolam in children, despite preliminary evidence suggesting its efficacy and safety. Further research is needed to address knowledge gaps, establish standardized protocols, and ensure the optimal utilization of remimazolam in pediatric sedation and anesthesia.…”
Section: Discussionmentioning
confidence: 85%
“…Remimazolam does not cause the infusion pain experienced with propofol and can be reversed with flumazenil. It can be used in patients with elevated CK levels, as in this case, without causing side effects, such as propofol infusion syndrome or rhabdomyolysis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, women had a higher incidence of anaphylaxis during anesthesia than males [ 8 ]. In addition, a recent review identified higher BMI, older age, and low plasma albumin concentration as risk factors for delayed emergence [ 26 ]. The influence of gender is known to be minimal in the pharmacokinetic and pharmacodynamic effects of remimazolam [ 27 ].…”
Section: Discussionmentioning
confidence: 99%